2020
DOI: 10.1007/s10658-020-01990-2
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of ring nematodes of the genus Criconemoides (Nematoda: Criconematidae) based on three new species from China, using integrative taxonomy

Abstract: Ring nematodes of the genus Criconemoides are a group of polyphagous, migratory rootectoparasites of plants. In a nematological survey of Zhejiang Province, three new Criconemoides species were isolated from the rhizosphere of Citrus sp., Euonymus alatus and Pterocarya stenoptera trees. In the present study, the new species characterized using an integrative taxonomic approach and described as Criconemoides parainformis n. sp., C. geraerti n. sp. and C. rotundicaudatus n. sp. Three of the species shares trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…Moreover, at that time, the genus Criconemella represented one of the largest groups of plant-parasitic nematodes (Barker, 1982 andIbrahim et al, 2000). That is because prior to the revision by Luc & Raski (1981), species included in this genus had been placed in six genera: Macroposthonia, Criconemoides, Xenocriconemella, Mesocriconema, Neocriconema, and Madinema. Current status of ring nematodes: Although the family Criconematidae currently contains 18 genera and five subfamilies (Geraert, 2010), most of them were characterized based on traditional data (Maria et al, 2020). Moreover, a few researchers have obtained low to moderate numbers of criconematids by extraction methods (Baermann funnel, Christie-Perry method) that depend on nematode motility, but in-depth studies of these (Barker, 1982 andMaria et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, at that time, the genus Criconemella represented one of the largest groups of plant-parasitic nematodes (Barker, 1982 andIbrahim et al, 2000). That is because prior to the revision by Luc & Raski (1981), species included in this genus had been placed in six genera: Macroposthonia, Criconemoides, Xenocriconemella, Mesocriconema, Neocriconema, and Madinema. Current status of ring nematodes: Although the family Criconematidae currently contains 18 genera and five subfamilies (Geraert, 2010), most of them were characterized based on traditional data (Maria et al, 2020). Moreover, a few researchers have obtained low to moderate numbers of criconematids by extraction methods (Baermann funnel, Christie-Perry method) that depend on nematode motility, but in-depth studies of these (Barker, 1982 andMaria et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Powers et al (2017) provided the 18S phylogenetic classification of Criconematoidea and discussed the taxonomic placement of several species. More recently, species diversity of ring nematodes of the genus Criconemoides was recently investigated using integrative taxonomy (Maria et al, 2020). Such investigations demonstrated that morphological studies coupled with other recent technological tools are helpful to avoid the previous confusions in generic and species levels and are useful to soundly grasp the phylogenetic relationships of criconematids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are not related to other serial structures of the body. In some cases, these rings are irregularly formed and a spiral arrangement can be deduced from the figures of the publications of, for example, Decraemer (1985), Figures 1, 6, and 7), Urbancik et al (1996), Figure 1), Hoschitz, Buchholz & Ott (1999, figures 19, 20, 29), Karssen and van Aelst (2002), Figure 3), Powers et al (2016), Figure 7), and Maria et al (2020), Figure 7) (see Figure 9c).…”
Section: Helicomery In Other Taxa With Serial Structures Along the Anteroposterior Body Axismentioning
confidence: 96%
“…(c) The tapeworm Moniezia expansa Rudolphi, 1810 ventral view, righthanded spiral (after Child, 1900). In all images, the beginning of the spiral is marked with an arrow, the end with an asterisk Figure 1), Hoschitz, Buchholz & Ott (1999, figures 19, 20, 29), Karssen and van Aelst (2002), Figure 3), Powers et al (2016), Figure 7), and Maria et al (2020), Figure 7) (see Figure 9c).…”
Section: Helicomery In Other Taxa With Serial Structures Along the Anteroposterior Body Axismentioning
confidence: 99%